Performance evaluation on key techniques for 5G enhanced mobile broadband - Longchang ZHU; Xiaodong JI; Xinran ZHANG; Quxin LI (Dianxin kexue)
The 5G eMBB scenario puts high requirements on performance such as spectrum efficiency and system capacity.It was proposed to introduce technologies such as massive MIMO and millimeter-wave communication,and combine heterogeneous networks to improve system performance,because traditional technologies cannot bring about corresponding performance improvement.At the same time,there are few simulation evaluation results for the key technologies of the eMBB scenario,and the performance advantages of each technology cannot be explained from the perspective of simulation.The performance of massive MIMO with different antenna numbers by building a system-level simulation platform were evaluated,and the impact of the density and bias of micro BS in the mmWave frequency to the performance based on the results in the heterogeneous networks was summarized.It has great refer-ence value for parameter configuration and network construction of 5G network.